Health Industrialization. - Salgues, Bruno (Elsevier Science, 2016)
Health Industrialization discusses the way healthcare professionals distinguish between medicine, surgery, and diet and lifestyle guidelines. In other words, the ways that medicine aims to provide quantity of life. Men and women would rather remain in good health as long as possible and compensate for the deficiencies that crop up to the best of their abilities. Hence, they are looking for quality of life that results in tensions brought on by different objectives. This book hypothesizes that this tension is the cause of an industrialization of medicine or health that depends to a degree on the point-of-view we choose.